Formulasi dan Evaluasi Lotion Ekstrak Alpukat (Persea Americana) sebagai Pelembab Kulit - Iskandar, Benni; Sidabutar, Santa Eni BR; Leny, Leny (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Avocado (Persea americana) contains a lot of vitamin A, vitamin B, vitamin C and vitamin E which is good to be used in skin care. One of the cosmetics for skincare is lotion, which is a liquid emulsion consisting of oil phase and water phase stabilized by emulgator. Lotion is used to protect and maintain skin moisture level. The purpose of this research was to formulate and evaluate the lotion in order to assure the physical characteristic and stability were accepted according to the Handbook of Pharmaceutical Excipients and Indonesia Pharmacopeia requirements.Formulation were made by using these following ingredients: glyceryl monostearate, cera alba, tween 80, glycerin, liquid paraffin, benzyl alcohol, perfume, aquadest. The study used 2 variation of concentration, which is Â 0.5% and 1% avocado extract as active substance, besides there is variations in glyceryl monostearate (5.5% and 5.7%), cera alba (2.7% and 2.9%), tween 80 (3.5% and 3.7%), glycerin (10% and 12%), liquid paraffin (10% and 12%), and benzyl alcohol (0.15% and 0.17%) in formulations I and II. Lotion was then tested for its physical properties, which include organoleptic test, homogeneity test, pH test, and spreadability test, lastly hedonic and irritation test were also being examined.Based on the results of physical properties test, both lotion formulations showed a viscous texture, beige and dark beige color with a distinctive odor, homogeneous, not irritating, have a pH value in the range of 4.55-5.31 with 4.9-5.15 cm spread. In the hedonic test on 10 panelists, lotion I formulation gave the most satisfaction score and comforty from respondents. Respondent's satisfaction on the appearance comprise the texture, color, and odor. Besides, viscosity and spreadability were also marked as how comfort the lotion is when it was applied to the respondentâ€™s skin.Keywords :Â Avocado, Extract, Lotion, Cosmetic, Moisturizer